Effects of Practice on Variability of Muscle Force. Issue 2 (April 2015) - Chung-Hoon, Kaiwi; Tracy, Brian L.; Marcus, Robin; Dibble, Lee; Burgess, Paul; Lastayo, Paul C.
The motor skill required to decrease the variability in muscle force steadiness can be challenging. The purposes of this study were to determine whether muscle force steadiness improved following repeated trials and whether the number of trials varied for healthy younger adults, healthy older adults, and older adults who have fallen to obtain stable muscle force steadiness measures. Sixty participants performed 30 concentric and eccentric contractions of the knee extensors on an isokinetic dynamometer. Each group had significant improvements in muscle force steadiness and obtained stable measures within six to nine trials. Healthy younger and older adults, and older adults who have fallen, can improve muscle force steadiness. These findings provide a framework for methodological approaches when testing steadiness in varying populations.